2007
DOI: 10.1073/pnas.0610451104
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria of the genus Asaia stably associate with Anopheles stephensi , an Asian malarial mosquito vector

Abstract: Here, we show that an ␣-proteobacterium of the genus Asaia is stably associated with larvae and adults of Anopheles stephensi, an important mosquito vector of Plasmodium vivax, a main malaria agent in Asia. Asaia bacteria dominate mosquito-associated microbiota, as shown by 16S rRNA gene abundance, quantitative PCR, transmission electron microscopy and in situ-hybridization of 16S rRNA genes. In adult mosquitoes, Asaia sp. is present in high population density in the female gut and in the male reproductive tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
578
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 412 publications
(600 citation statements)
references
References 38 publications
15
578
0
7
Order By: Relevance
“…Recently, Favia et al (2007) reported that the main bacteria species associated with adults and larvae of the mosquito Anopheles stephensi are from the genus Asaia, that is related to acetic acid bacteria. They found Asaia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Favia et al (2007) reported that the main bacteria species associated with adults and larvae of the mosquito Anopheles stephensi are from the genus Asaia, that is related to acetic acid bacteria. They found Asaia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Asaia bacteria naturally infect the Anopheles germ line and are vertically transmitted (39,40), and thus may conflict with other maternally transmitted bacteria. This, together with the observed significant and large decrease in frequency of this taxon upon antibiotic treatment in both mosquito species, led us to investigate Asaia as a candidate bacteria involved in the interference of Wolbachia transmission.…”
Section: Microbiota-wolbachia Interactions Kill Mosquitoes After a Bloodmentioning
confidence: 99%
“…Indeed, sexually transmitted strains were observed to take over from existing infections following such a coinfection event. The study of aphid secondary symbionts complements previous work describing male-to-female sexual transmission for a variety of viral and microsporidial associates of insects that also showed maternal inheritance (reviewed in Knell and Webberley 2004), records of a low level of paternal transmission for Wolbachia (Hoffmann and Turelli 1988), and a more recent record of sexual transmission of the bacterium Asaia that is maternally inherited in Anopheles mosquitoes (Favia et al 2007). …”
Section: Introductionmentioning
confidence: 48%
“…This suggests that constraint is the main reason secondary symbionts do not degrade into feminizers. Indeed, there are many fewer records of host species infected with feminizers (two insect species and a variety of Crustacea; Bouchon et al 1998;Hiroki et al 2002;Terry et al 2004;Negri et al 2006;Favia et al 2007) and even fewer microorganisms that have evolved this trait (Wolbachia, microsporidia).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation